The Hunger Vital Sign Identifies Household Food Insecurity among Children in Emergency Departments and Primary Care - Rajender K. Gattu; Grace Paik; Yan Wang; Prema Ray; Richard Lichenstein; Maureen M. Black (MDPI AG, 2019)
This study aimed: (1) to examine the sensitivity and specificity of the 2-item Hunger Vital Sign against the 18-item Household Food Security Survey Module (HFSSM) in identifying young children in food insecure households in emergency department and primary care sites and (2) to examine associations between food insecurity and adverse health conditions. We conducted cross-sectional surveys from 2009−2017 among 5039 caregivers of children age <48 months. We measured adverse child health by caregiver-reported perceived health, prior hospitalizations, and developmental risk (Parents’ Evaluation of Developmental Status). Analyses were conducted using covariate-adjusted logistic regression. Sensitivity and specificity of the Hunger Vital Sign against the HFSSM were 96.7% and 86.2%. Using the HFSSM, children in the emergency department had a 28% increase in the odds of experiencing food insecurity, compared to children in primary care, aOR = 1.28, 95% Confidence Interval (CI) = 1.08−1.52, p = 0.005. Using the Hunger Vital Sign, the increase was 26%, aOR = 1.26, 95% CI = 1.08−1.46, and p = 0.003. The odds of children’s adverse health conditions were significantly greater in food insecure households, compared to food secure households, using either HFSSM or the Hunger Vital Sign. Screening for food insecurity with the Hunger Vital Sign identifies children at risk for adverse health conditions in both primary care and emergency department sites, and can be used to connect families with resources to alleviate food insecurity.